(untitled) (Biological Sciences - PJSIR, 2016)
Freshly harvested, matured, newly ripe pawpaw (Carica papaya) fruit (Maradol variety) was stored at room temperature (27±1 °C) for 7days. The seeds of the freshly harvested and stored pawpaw fruit were taken and divided into two groups each; one was dried as dry sample, dry freshly harvested sample (DFHS) and dry stored sample (DSS) while the other was left as wet sample, wet freshly harvested sample (WFHS) and wet stored sample (WSS). The bioactive components, antioxidative properties and inhibition of Fe2+ induced lipid peroxidation activity of the water extract of the seed were investigated. Storage of pawpaw fruit caused a significant increase in ascorbic acid and flavonoid content of the pawpaw seed in both dry and wet samples but only in dry stored sample significant increase in the phenol content of the seed was observed. The dried pawpaw seed DFHS and DSS showed stronger inhibition of Fe2+ induced lipid peroxidation activities.